Intervensi untuk mengatasi rasa haus pada pasien penyakit ginjal kronis yang menjalani hemodialisis: A scoping review - Sridiawati, Esy; Ibrahim, Kusman; Pratiwi, Sri Hartati (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Patients with chronic kidney disease (CKD) often experience thirst when restricting their fluid intake. To improve patient survival, interventions to manage thirst in hemodialysis patients are needed, with the hope of reducing fluid intake in HD patients. Thirst remains an unresolved issue in hemodialysis (HD) patients. Purpose: To map and synthesize the current evidence on interventions to manage thirst in chronic kidney disease (CKD) patients undergoing hemodialysis. Method: A scoping review was conducted using the PRISMA-ScR framework. Articles were identified through PubMed, Scopus, EBSCOhost, and Google Scholar using keywords related to